The Effect of Price, Financial Condition, and Lifestyle on Cigarette Purchasing Decisions in Batam City - Hidayat, M. Alvi; Arpah, M.; Maizar, Maizar (Journal of Innovative and Creativity, 2026)
Purpose. This study aims to analyze the effect of price, financial condition, and lifestyle on cigarette purchasing decisions among consumers in Batam City. Consumer purchasing decisions are influenced by various economic and behavioral factors that shape individual consumption patterns. Price is often considered a critical determinant because it reflects the cost that consumers must bear to obtain a product. Financial condition represents the economic capability of consumers in fulfilling their consumption needs, while lifestyle reflects patterns of activities, interests, and social interactions that influence consumption behavior. In the context of cigarette consumption, these factors may shape how consumers evaluate and decide to purchase cigarette products. Therefore, understanding the influence of price, financial condition, and lifestyle is important for explaining consumer purchasing behavior in the cigarette market. Materials and methods. This research applied a quantitative explanatory approach using a survey method. The population of this study consisted of cigarette consumers in Batam City. A total of 100 respondents were selected using an accidental sampling technique. Data were gathered through a structured questionnaire designed using a five-point Likert scale to measure each research variable. Prior to hypothesis testing, the research instrument was examined through validity and reliability tests to ensure that the measurement items were accurate and consistent. Classical assumption tests, including normality, multicollinearity, and heteroscedasticity tests, were conducted to verify that the regression model fulfilled the required statistical assumptions. Multiple linear regression analysis was then used to evaluate the effect of the independent variables on cigarette purchasing decisions through t-tests, F-tests, and the coefficient of determination (R²) using SPSS software. Results. The results of the analysis indicate that price has a positive and statistically significant effect on cigarette purchasing decisions (Sig.=0.000). Lifestyle also demonstrates a positive and significant influence on purchasing decisions (Sig.=0.000). However, financial condition does not show a statistically significant effect on cigarette purchasing decisions (Sig.=0.542). The simultaneous test shows that price, financial condition, and lifestyle collectively have a significant influence on cigarette purchasing decisions (F-test Sig.=0.000). The regression model indicates a strong relationship between the variables, with the coefficient of determination showing that approximately 80.4% of the variation in purchasing decisions can be explained by the independent variables included in the model. Conclusions. The findings of this study indicate that price and lifestyle play an important role in influencing cigarette purchasing decisions among consumers in Batam City. Although financial condition does not show a significant effect, the combined influence of economic and lifestyle factors remains important in shaping consumer purchasing behavior. These results highlight the importance of considering both economic considerations and lifestyle characteristics when analyzing cigarette consumption patterns.